Melittofauna and Other Potential Pollinators in Wetland and Uplands in South Central Nebraska (Insecta: Apoidea) - Park, Cynthia N.; Overall, Lisa M.; Smith, Loren M.; Lagrange, Ted; Mcmurry, Scott (Zootaxa, 2017)
Our objective was to document potential wild pollinating insects in south central Nebraska. This intensively cultivated region is known as the Rainwater Basin and contains some of the most endangered wetland systems in North America. We used blue vane traps to passively collect insects and insect nets to actively collect on flowering plants from April through October in 2014 and 2015. Habitat types included playa wetlands, adjacent mixed and tallgrass prairies, and agricultural fields. Over 112,000 insects were collected; Hymenoptera represented 78% of the total, and the families Apidae and Halictidae comprised 99% of the total melittofauna. Insects from 13 orders were collected, but Hymenoptera, Diptera, and Coleoptera were the most abundant potential pollinators.